Optimization of Camel Milk Cheese Processing Using Protease from Latex (Ficus carica) - Fguiri, Imen; Sboui, Amel; Ziadi, Manel; Ayeb, Naziha; Arroum, Samira; Dbara, Mohamed; Hammadi, Mohamed; Khorchani, Touhami (Research Aspects in Agriculture and Veterinary Science Vol. 5, 2022)
This study aimed to prospect latex fractions from Ficus carica for new plant peptidases with milk-clotting activities of camel milk, for use as rennet alternatives. The enzymatic preparation was obtained by fractionation of latex from fig tree by Fast Protein Liquid Chromatography (FPLC). In the manufacturing process, the milk is pasteurized at low temperature and cooled, it was added a culture of lactic starters isolated from artisanal fermented milk, subsequently it is added the enzymatic preparation of latex; the mixture is incubated for 24 hours at 37°C; after coagulation, the whey is drained to obtain a cheese curd; finally, the mixture is cooled to obtain a fresh cheese. The cheese yield is determined at different doses of fractions and it was found that 1ml of the extract in 100 ml of camel milk gives a yield of 15%. The physicochemical and microbiological characterization of camel milk cheese compared to cow milk cheese showed that camel milk cheese was more acidic, richer in protein (50,04 g/l) and phosphorus (0.199 g/l) but less loaded with total mesophilic flora. Camel milk cheese has higher levels of fat-soluble vitamins (retinol, K2 and Tocopherol), a high content of ascorbic acid (6.189 mg / kg) compared to cow milk cheese. The major fatty acid present in camel milk cheese is oleic acid (28.4%) followed by palmitic acid (27.1%) and stearic acid (23.6%).